2018
DOI: 10.1002/ddr.21492
|View full text |Cite
|
Sign up to set email alerts
|

Microsponge: An emerging drug delivery strategy

Abstract: Microsponges are the spherical particles ranging from 5 to 300 μm in size. These are further made up of clusters of smaller spheres. They are designed for delivering the drug efficiently at a comparatively lesser dose and enhancing the stability, modifying the drug release profile and minimizing the side effects. Microsponge drug delivery system decrease transdermal invasion of the active ingredient into the skin while increasing the time the drug remains on the skin surface or within the epidermis. Preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The cytokines cause reflective pathological changes in the advancement of hepatotoxicity. [50][51][52] Frequently, we found that CCl 4 suggestively expanded TNF-α, IL-1β, and IL-6 expression. 53,54 Interestingly, Met or Lut, especially in combination, expressively decreased the downstreaming inflammatory cascade.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The cytokines cause reflective pathological changes in the advancement of hepatotoxicity. [50][51][52] Frequently, we found that CCl 4 suggestively expanded TNF-α, IL-1β, and IL-6 expression. 53,54 Interestingly, Met or Lut, especially in combination, expressively decreased the downstreaming inflammatory cascade.…”
Section: Discussionmentioning
confidence: 64%
“…Prior studies have referenced that CCl 4 worsens successions of inflammatory responses in the nearby zone of hepatic tissues by invigorating generation of inflammatory cytokines. The cytokines cause reflective pathological changes in the advancement of hepatotoxicity . Frequently, we found that CCl 4 suggestively expanded TNF‐α, IL‐1β, and IL‐6 expression .…”
Section: Discussionmentioning
confidence: 75%
“…24 Schematic representation of the process is shown in Figure 3. 24,25 ''Quasi emulsion solvent diffusion'' 25 technique: Internal organic phase when dispersed in aqueous phase it forms the globules; further diffusion of solvent results in leaving the structure porous. The detailed description is given below with schematic representation in Figure 4.…”
Section: Methods For Preparation Of Microspongesmentioning
confidence: 99%
“…The detailed description is given below with schematic representation in Figure 4. 25 • Preparation of Internal phase: It is an organic solution formed by dissolving drug, polymer and plasticizer in a miscible inert organic solvent. If necessary it is sonicated.…”
Section: Methods For Preparation Of Microspongesmentioning
confidence: 99%
“…The search for another hopeful conceivably engaged with MH drove us to the TRPV1 channel. To date, despite the fact that assuming a broadly acknowledged role in nociception, this channel is not plainly connected to any inherited disease . Endeavors have been mostly centered around its suggestion in chronic pain disorders .…”
Section: Trp Channelsmentioning
confidence: 99%